POLA PERGERAKAN DAN WILAYAH JELAJAH GAJAH SUMATRA (Elephas maximus sumatranus Temminck, 1874) DENGAN MENGGUNAKAN GPS RADIO COLLAR DI KAWASAN TESSO NILO, RIAU - Dwi Adhari Nugraha; Haris Gunawan; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The Sumatran elephant is the largest land mammal species still left on the island of Sumatra and is currently critically endangered. One of the remaining habitats for Sumatran elephant in Sumatra is Tesso Nilo. Conversion of land around Tesso Nilo becomes a plantation and settlement causing conflicts between humans and elephants increased. This research was conducted from May 2013 to June 2014 around Tesso Nilo National Park (TNTN) to determine the patterns of movement and homerange of Sumatran elephants in habitats that have been interfered by human activities using GPSRadio Collar technology and GIS analysis. The data was processed with Excel and Arcgis Ver. 10.1 program. The results showed that the patterns of the daily movement of elephants was random with an homerange area of 22.362,27 ha and consisted of various types of land.